Eksplorasi Persepsi Konsumen Terhadap Strategi Price Discount (Promo Super Si Gayan) Supermarket Tiara Dewata Denpasar - I Putu Adi Surya; Candraningrat (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This research is motivated by changes in consumer behavior after the COVID-19 pandemic who are increasingly sensitive to prices and selective in responding to promotions. Tiara Dewata Supermarket in Denpasar launched the